Fiscal policy shocks and stock prices in the United States - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2017)
This paper uses a range of structural VARs to show that the response of US stock prices to fiscal shocks changed in 1980. Over the period 1955-1980 an expansionary spending or revenue shock was associated with modestly higher stock prices. After 1980, along with a decline in the fiscal multiplier, the response of stock prices to the same shock became negative and larger in magnitude. We use an estimated DSGE model to show that this change is consistent with a switch from an economy characterised by active fiscal policy and passive monetary policy to one where fiscal policy was passive and the central bank acted aggressively in response to inflationary shocks.
Keywords: C5; E1; E5; E6; 330; Fiscal policy shocks; Stock prices; VAR; DSGE